Enduring questions using Jewish children's literature in classrooms - Bloome, David; Freeman, Evelyn B. 1948-; Horowitz, Rosemary; Katz, Laurie (Rowman & Littlefield, 2023)
"This book introduces preschool and elementary teachers to a broad range of high-quality children's literature books and stories and provides them with background information so that they can use Jewish children's literature thoughtfully with their students"--
Keywords: Jüdische Literatur; Lehrstoff; Kinderliteratur; Antisemitismus; Geschichte; Religion; Literaturunterricht; Judentum; Judenvernichtung; Englisch; Children's literature / Study and teaching (Preschool); Children's literature / Study and teaching (Elementary); Judaism / Study and teaching (Preschool); Judaism / Study and teaching (Elementary); Jewish children / Books and reading; Jewish literature